Behavioral Prospects of Individual Investor Decision Making Process: A Review - Raut, Rajdeep Kumar; Das, Niladri (Indian Journal of Finance, 2015)
The bounded rationality of human behavior has become the most prominent issue nowadays for the researchers of applied economics and finance. A lot of evidence is available that shows the psychological and social patterns merging with individuals’ capital markets investing behaviour that nullifies the well established theories and models of modern finance. The modern financial models like CAPM argue that the investors are fully rational, and the market is fully efficient as no individual can take the advantage of arbitraging. Studies advocating behavioral finance have confirmed social influences and psychological biases which deviate individual investors from their calculated and predetermined decisions, and reject the hypothesis of individuals being fully rational while taking decisions related to stock markets. Through this review paper, the concepts related to behavioral finance were illustrated by using various studies, and a conceptual framework showed the influential factors related to behavioral changes impacting the individual investors’ decision making, that is, creating irrational investors and inefficient markets. Through the review of various studies, we observed that social factors like herding, emotional contagion, imitation, and information cascades along with psychological patterns like representativeness availability and anchoring heuristics are the basic key factors that determine individual decisions. This paper highlighted the common decisional errors made by investors, and the study will be useful for investors and portfolio managers as it will aid them in making their choices keeping the discussed behavioral biases in mind.